METAPHOR IN COLDPLAY-FIX YOU LYRICS: COGNITIVE SEMANTICS ANALYSIS - Dewi, Shafira Anastasya (ReALL - Research on Applied Linguistics and Literature, 2025)
This research analyzes the metaphorical meanings in the lyrics of Coldplay's song "Fix You" using a cognitive semantics approach, specifically the theories of Lakoff and Johnson (2003) for conceptual metaphors and Croft and Cruse (2004) for image schemas. The study aims to uncover the hidden meanings within the lyrics and understand how the songwriter, Chris Martin, conveys messages through figurative language. The methodology involves listening to the song lyrics, noting down relevant phrases, and then performing a descriptive analysis. The findings reveal two types of conceptual metaphors: orientational and ontological. Out of nine analyzed song lyrics, seven were identified as ontological metaphors and two as orientational metaphors. Correspondingly, the image schema analysis identified two space image schemes, one identity image scheme, and six existence image schemes. The research concludes that the lyrics of "Fix You" metaphorically depict someone navigating difficult times and seeking reunion after loss, using physical and abstract concepts to allow for varied interpretations by listeners.